A Critical Analysis of Enabler’s Function in Malaysia Halal Meat Industry - Yaacob, Teh Zaharah; Abd Razak, Siti Suraya (INSLA E-Proceedings, 2020)
Halal meat supply chain operation involved the coordination of various stakeholders within the supply chain operation. Every stakeholder in the chain including the enablers plays an important function to ensure the supply chain efficiency, sustainability, integrity and conformance to the policies and compliance. The aim of the paper is to critically analyse the function of enablers as the government executor problem solving for the enforcement of the regulations and policies. Thestudy reviewsthe currentliteratureandlegislative framework in Malaysia which is in place in halal meat supply chain operation. A thorough review of Act’s and Standards were conducted with the application of Stakeholder Theory to determine the function of enablers as the policies executor for the government in the halal meat supply chain. The findings of this study reveal the issues of enforcement, and monitoring that had conflicted the flow of the chain process. The problems occurred from the enforcement and regulations are being highlighted as to clarify the function of the enablers as the policy executors.